PENGARUH MEDIA SOSIAL TERHADAP KEBIASAAN BERKATA KASAR PADA ANAK DALAM PERSPEKTIF PENDIDIKAN ISLAM - Hasan Yusuf; Hilmi Saepul Haq; Hilwa Ribatul Khoil; Alfi Zakiyah (STAI Pelabuhan Ratu, 2026)
The rapid development of social media has had a significant impact on various aspects of children's lives, including their language habits. This study is motivated by the increasing use of harsh language among children, which is associated with the easy access to digital content through social media. The focus of this research is to analyze the influence of social media on children’s use of inappropriate language and to examine it from the perspective of Islamic education. This study employs a qualitative approach using a literature review method based on various relevant scientific journals. The findings indicate that children tend to imitate language found in digital content and online interactions, particularly when social media is used intensively without adequate supervision. In addition, social media usage also contributes to the decline in language politeness among children. From the perspective of Islamic education, the use of polite language is considered an integral part of developing noble character, which should be instilled from an early age through habituation and role modeling. Therefore, active involvement from parents and educators is necessary in providing supervision, promoting digital literacy, and instilling Islamic values so that children are able to communicate appropriately in accordance with religious and social norms.